ANTIFUNGAL AND ANTI-INFLAMMATORY EFFECTS OF COPTIDIS RHIZOMA EXTRACT AGAINST CANDIDA ALBICANS - Yang, Yi; Ning, Yumei; Zhu, Xiuzhi; Li, Ruilan; Ye, Huijun; Zhao, Lei; Jin, Lihua; Zhou, Xiaomei (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Rhizoma Coptidis has been used as antibiotics in traditional Chinese medicine practice for many years. Here, we examined the effect of Rhizoma Coptidis extract on the growth of C. albicans. Materials and Methods: The antifungal effects of Coptidis Rhizoma extract was examined by time-kill assay, transmission electron microscope (TEM) and scanning electron microscope (SEM) observations. The anti-inflammatory effect of the Rhizoma Coptidis extract was examined in mouse model of Candida vaginitis. Results: We found that the MIC of Coptidis Rhizoma extract was 3.125 mg/mL. The time-kill assay suggested that Rhizoma Coptidis extract could inhibit the growth of C. albicans. The SEM and TEM observations showed notable changes of cell wall and cytoplasmic content of the C. albicans and complete collapse of yeast cell exposed to Rhizoma Coptidis extract. Our in vivo antifungal activity studies in mouse model of Candidal vaginitis showed the reduction of inflammatory reaction was found after Rhizoma Coptidis extract treatment. In addition, the COX-2 expression was decreased in mice treated with Coptidis Rhizoma extract as compared with the control mice. Conclusion: Our results indicate that Coptidis Rhizoma extract is a promising candidate in candidal vaginitis treatment in the future.